Physicochemical Properties and Sensory Acceptance of a Bromelain-Hydrolyzed Oyster, Oyster Mushroom, and Tomato-Based Seasoning Powder Rich in Zinc and Glutamic Acid - Florietta Sabrina; Yunita Satya Pratiwi; Dianita Kumalasari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The increasing demand for natural flavor enhancers has encouraged the development of alternatives to synthetic monosodium glutamate (MSG). This study evaluated the physicochemical properties and sensory acceptance of a bromelain-hydrolyzed seasoning powder formulated from oyster (Crassostrea sp.), oyster mushroom (Pleurotus ostreatus), and tomato (Solanum lycopersicum) with the addition of spices. A completely randomized factorial design was applied using two factors: the proportion of oyster, oyster mushroom, and tomato, and spice concentration. The evaluated parameters included protein content, moisture content, ash content, water solubility index (WSI), yield, sensory acceptance, zinc content, and glutamic acid content. The results showed that raw material proportion significantly affected all physicochemical characteristics, while spice concentration significantly influenced protein content and WSI. Significant interactions between both factors were observed for moisture content, ash content, and yield. Sensory evaluation indicated significant differences in taste and overall acceptance among treatments. The optimum formulation consisted of oyster, oyster mushroom, and tomato in a 40:40:20 proportion, with a 3% spice concentration, producing a seasoning powder containing 15.30% protein, 3.98% moisture, 6.75% ash, 20.75% yield, 166.7 mg/kg zinc, and 18,307.70 ppm glutamic acid. These findings demonstrate the potential of bromelain hydrolysis to produce a natural seasoning powder rich in zinc and glutamic acid, with desirable physicochemical and sensory characteristics; the appetite-supporting potential suggested by these compounds remains hypothetical and requires confirmation through future biological or clinical studies. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and Production